Marital status, telomere length and cardiovascular disease risk in a Swedish prospective cohort. Issue 4 (14th November 2019) - Chen, Ruoqing; Zhan, Yiqiang; Pedersen, Nancy; Fall, Katja; Valdimarsdóttir, Unnur A; Hägg, Sara; Fang, Fang
Abstract : Objective: To investigate if marital status is associated with risk of cardiovascular disease (CVD) and to explore the potential influence of leucocyte telomere length (LTL), a marker of biological ageing, on such association. Design: Population-based prospective cohort study Settings: Swedish Twin Registry. Participants: Based on the Screening Across the Lifespan Twin Study from the Swedish Twin Registry, we included 10 058 twins born between 1900 and 1958 who underwent an interview between 1998 and 2002 during which information about marital status was collected. Blood samples from these participants were subsequently collected between 2004 and 2008 and used for LTL assessment using quantitative PCR technique. Main outcome measures: Incident cases of CVD were identified through the Swedish Patient Register and Causes of Death Register through December 31, 2016. Multivariable linear regression and Cox proportional hazards regression models were used to estimate the regression coefficients (βs) and HRs with 95% CIs respectively. Potential confounders included age, sex, educational attainment and body mass index. Results: A total of 2010 participants were diagnosed with CVD during a median follow-up of 9.8 years. LTL was shorter among individuals living singly, including those who were divorced or separated (β:−0.014, 95% CI: −0.035, 0.007), widowed (β:−0.035, 95% CI: −0.061, –0.010), or living alone (β:−0.033, 95% CI: −0.052, –0.014), than individuals who were married or cohabitating. One SD increase of LTL was associated with a lower risk of CVD (HR: 0.79, 95% CI: 0.66, 0.93). Individuals who were divorced or separated, widowed, or living alone had a higher risk of CVD than individuals who were married or cohabitating. The summary HR of CVD was 1.21 (95% CI: 1.08, 1.35) when comparing individuals who were living singly, regardless of reason, with the individuals who were married or cohabitating. LTL appeared to mediate little of the association between marital status and CVD (HR additionally adjusted for LTL: 1.20; 95% CI: 1.08, 1.34). Conclusions: Living singly, regardless of reason, was associated with a shorter LTL and a higher risk of CVD. The association between marital status and CVD was however not greatly attributable to telomere shortening.